Synthesis of a macrocyclic Ligand, Me4-[16]-Tetraene-N4 and its Metal Complexes with Chromium, Iron, Cobalt and Nickel - Rai, H.C.; Kumar, Ashwini; Kumari, Anuradha (Asian Journal of Chemistry, 2010)
A series of metal complexes of chromium, iron, cobalt and nickel with a macrocyclic ligand 6,8,14,16-Me4-[16]-6,8,14,16-tetraene- 1,5,9,13-N4 has been prepared and characterized on the basis of infrared, electronic, PMR spectral studies as well as conductivity and magnetic moment studies. The ligand reacts with metal (II) acetates under conditions of non-aqueous chelation to give the nautral macrocyclic complex M(Me4-[ 16]-tetraenato-(2-)N4). (M=Cr, Fe, Co or Ni).